2009
DOI: 10.1111/j.1749-6632.2008.03658.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptides Modulate the Heart of the Stick Insect Baculum extradentatum

Abstract: The dorsal vessel of the stick insect Baculum extradentatum consists of a tubular heart and an aorta that extends anteriorly into the head. Alary muscles, associated with the heart, are anchored to the body wall with attachments to the dorsal diaphragm. Alary muscle contraction draws hemolymph into the heart through incurrent ostia. Hemolymph exits the heart through the excurrent ostia present on the dorsal vessel in thoracic and abdominal segments. FMRFamide-related peptides are present in axons of the segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The pentapeptide proctolin (RYLPT‐OH) was the first insect neuropeptide identified from whole body extracts of P. americana where it is associated with myostimulatory action on hindgut visceral muscles (Starratt & Brown, 1975). Proctolin has been identified subsequently in many other insects and other arthropods, and is a highly potent stimulator of a variety of visceral and skeletal muscles, including the dorsal heart (Orchard et al , 1989; Lange & Orchard, 2006; Lange et al , 2009). Moreover, proctolin is the most potent myostimulatory neuropeptide in the antennal circulatory system of P. americana , and its functional relevance as a peptide transmitter acting via a decrease of the K + ‐conductance is demonstrated (Hertel et al , 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The pentapeptide proctolin (RYLPT‐OH) was the first insect neuropeptide identified from whole body extracts of P. americana where it is associated with myostimulatory action on hindgut visceral muscles (Starratt & Brown, 1975). Proctolin has been identified subsequently in many other insects and other arthropods, and is a highly potent stimulator of a variety of visceral and skeletal muscles, including the dorsal heart (Orchard et al , 1989; Lange & Orchard, 2006; Lange et al , 2009). Moreover, proctolin is the most potent myostimulatory neuropeptide in the antennal circulatory system of P. americana , and its functional relevance as a peptide transmitter acting via a decrease of the K + ‐conductance is demonstrated (Hertel et al , 1997).…”
Section: Introductionmentioning
confidence: 99%
“…26,32 The innervation to B. extradentatum dorsal vessel contains other neuropeptides families, including CCAP and proctolin 16,17 and these peptides accelerate heart beat frequency. The staining pattern for FLI shares some similarity with the staining pattern for proctolin and CCAP in B. extradentatum, 16,18 although at present we do not know which members of the FaRP family are actually present. Thus, CCAP-like, proctolin-like and FLI are present within processes over the incurrent ostia and alary muscles.…”
Section: Dovepressmentioning
confidence: 75%
“…For example, a number of studies have reported the presence of crustacean cardioactive peptide (CCAP), proctolin, and FMRFamiderelated peptides (FaRPs) with the innervation to the dorsal vessel in insects, and have demonstrated effects on heart beat frequency. [16][17][18][19][20][21][22] In addition, the presence of excurrent ostia suggests another form of microcirculatory control, and if these excurrent ostia are controlled (opened and closed) then microcirculatory pathways can be established. This control is suggested by the recent demonstration that the excurrent ostia in B. extradentatum stains with F-actin, indicating the presence of muscle cells.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…FaLPs signaling has been studied in variety of insect species, including mosquitoes (Hillyer et al, 2014), stick insects (Lange et al, 2009), kissing bugs (Sedra and Lange, 2014), or flies (Merte and Nichols, 2002). However, the receptor for FaLPs was first discovered (Cazzamali and Grimmelikhuijzen, 2002) and very well characterized only in D. melanogaster (Maynard et al, 2013;Milakovic et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Other known functions of FaLPs include involvement in regulation of circadian rhythm (Pyza and Meinertzhagen, 2003) and synaptic activity (Marques et al, 2003). Most of the research has been performed on different insect species, such as flies (Merte and Nichols, 2002), locusts (Robb and Evans, 1994), stick insects (Lange et al, 2009), or mosquitoes (Hillyer et al, 2014). However, scarce information is available regarding FaLPs in the largest insect order -the beetles.…”
Section: Introductionmentioning
confidence: 99%